2018
DOI: 10.3389/fnhum.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

Speed-Dependent Modulation of Muscle Activity Based on Muscle Synergies during Treadmill Walking

Abstract: The regulation of walking speed is easily achieved. However, the central nervous system (CNS) must coordinate numerous muscles in order to achieve a smooth and continuous control of walking speed. To control walking speed appropriately, the CNS may need to utilize a simplified system for the control of numerous muscles. Previous studies have revealed that the CNS may control walking via muscle synergies that simplify the control of muscles by modularly organizing several muscles. We hypothesized that the CNS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 59 publications
3
48
0
Order By: Relevance
“…In addition, children with more severe types of CP generally walk slower compared to less affected and TD children. Walking speed is an important factor to consider when evaluating muscle synergies, as previous research found that both number and structure of synergies were affected by walking speed in healthy adults (Yokoyama et al, 2016 ; Kibushi et al, 2018 ) and TD children (Steele et al, 2015 ). These findings suggest that different walking speeds require different control from the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children with more severe types of CP generally walk slower compared to less affected and TD children. Walking speed is an important factor to consider when evaluating muscle synergies, as previous research found that both number and structure of synergies were affected by walking speed in healthy adults (Yokoyama et al, 2016 ; Kibushi et al, 2018 ) and TD children (Steele et al, 2015 ). These findings suggest that different walking speeds require different control from the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…To assess and quantify the similarity between the normalized values of the eight muscle groups measured across the directions on the static dynamometer and the weight value of the muscular synergies previously measured during gait in a group of healthy individuals [12], cosine similarity was used and the highest value was selected for each synergy [26]. Muscle weightings were categorized as similar when the cosine similarities were over 0.71 (p < 0.01).…”
Section: D4mentioning
confidence: 99%
“…Walking is one of the basic forms of human movement. This complex process consists of consequent steps, see Figure 4 and article by Kibushi et al [18]. A step is defined as a movement of the leg between the time points when the foot leaves the surface and touches it again.…”
Section: Description Of Walking Stagesmentioning
confidence: 99%